2015
DOI: 10.3109/13561820.2015.1010718
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of patient satisfaction outcomes in an interprofessional student-run free clinic

Abstract: As the evidence supporting the value of well-coordinated healthcare teams continues to grow, so to do the calls from medical educators and policy makers for the development of meaningful interprofessional educational experiences for health professions students. The student-run clinic has emerged as a unique venue for such experiential interprofessional learning experiences, with over 100 such clinics now in operation across North America. As the number and variety of these clinics rises, it has become increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…Consistent with our findings at SHAWCO, several studies have found high patient satisfaction ratings of student-run free clinics [6,[9][10][11]. Interestingly, SHAWCO patients rated medical students higher than physicians on listening to their concerns.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings at SHAWCO, several studies have found high patient satisfaction ratings of student-run free clinics [6,[9][10][11]. Interestingly, SHAWCO patients rated medical students higher than physicians on listening to their concerns.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies evaluating patient satisfaction at SRFCs have shown high satisfaction with care provided [6,9,10]. However, the patient perspective of care received at student-run free clinics has only recently been explored in a small number of studies, most taking place in affluent nations [10][11][12][13]. A recent South African study from Du Toit et al found high patient satisfaction with a mobile clinic for community-based service learning at Nelson Mandela University in the Eastern Cape province [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the result is consistent with the literature reporting correspondingly high levels of satisfaction expressed by patients receiving free care in a student clinic. 11…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence to support the idea that student-led free clinics can provide care at or above the standard of care; however, the literature discussing physical therapy specific outcomes is limited. 23,24,25 Adopting a student-led free clinic with an interprofessional approach into multiple schools' programs can be challenging. Logistically, schools may be separated by distance, variable student schedules, differing viewpoints and administrative hurdles, as well as the ability to procure financial resources.…”
Section: Challengesmentioning
confidence: 99%